Influence of process pressure on HW-CVD deposited a-Si : H films - Jadkar, Sandesh R.; Sali, J. V.; Kshirsagar, S. T.; Takwale, M. G. (Solar Energy Materials and Solar Cells, 2005)
Hydrogenated amorphous silicon (a-Si:H) films were deposited using pure silane (SiH4) without hydrogen dilution by hot wire chemical vapor deposition (HW-CVD) technique. The electrical, optical, and structural properties of these films are systematically studied as a function of process pressure (P-r). The device quality a-Si:H films with a photosensitivity > 10(5) were deposited at a deposition rate >40 Angstrom/s at low process pressure. However, a-Si:H films deposited at higher process pressures show degradation in their electrical and structural properties. The FTIR spectroscopic analysis showed that a-Si:H films deposited at low process pressure contain hydrogen mainly in mono-hydrogen (Si-H) configuration whereas films deposited at higher process pressure have hydrogen in di-hydrogen (Si-H-2) or poly hydrogen (SiH2)(n) complexes. The hydrogen content (C-H) in the films was found to be less than 4 at.% over the entire range of process pressure studied. This indicates that the growth of a-Si:H films is mainly from the atomic species (Si and H) evaporated from the hot filament and hydrogen gets incorporated in the film via gas-phase reactions and substrate gas interactions. The band gap, however was found similar to1.71 eV or much higher. We attribute high band gap at low hydrogen content may be due to presence of microvoids. Raman spectroscopic analysis showed increase in structural disorder and Rayleigh scattering with increase in the process pressure. (C) 2004 Elsevier B.V. All rights reserved.
2nd International Conference on Cat-CVD (Hot-Wire CVD) Process, DENVER, CO, SEP 10-14, 2002
Keywords: Electrical properties; FTIR spectroscopy; hot wire chemical vapor deposition; hydrogenated amorphous silicon; Raman spectroscopy